SKENARIO PEMANFAATAN LAHAN DI KECAMATAN MAPANGET BERDASARKAN ZONE AGROEKOLOGI DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) - Antoneta Kartini Kotangon; Johannes E. X. Rogi; Johan A. Rombang (Sam Ratulangi University, 2016)
This study aimed to develop land use scenarios in District Mapanget using Agroecology Zone-based Geographic Information System (GIS). The data used in this study are primary data and secondary data. Primary data were collected through surveys and direct observations in the field. The activities carried out field surveys to obtain state information field through taking pictures with a digital camera. Analysis of social data and data on potential farming is also done through the compilation of data to map the District Mapanget. Furthermore biophysical data agro-ecological, social and agricultural potential of the data compiled in a database system was using Quantum GIS program version 1.8. This study found that the use of agricultural land to non-agricultural land in the district Mapanget very difficult to avoid due to the low value of land from the agricultural sector compared to other sectors. So based on the evaluation conducted by comparing the map with a map of the existing condition of the District RTRW 2014-2034 Mapanget then it changes the function of which is no longer appropriate region where the agricultural area have been converted into non-agricultural. In order for this condition continues to be bad for the environment and agriculture will require efforts in the management and development in the District Mapanget, among others, the development of urban agriculture, every development in Sub Mapanget should always refer to the scenario Land use and Spatial plan of the District Mapanget that there are both carried out by the government, private or public. Urban agriculture has an important role for urban communities that suggested the need for land use scenarios in District Mapanget. Based on agroecological zone map and a map of the District RTRW 2014-2034 Mapanget then be collated Mapanget the District land use scenarios are divided by 3 (three) scenarios that city Scenario, Scenario frame the city, urban-rural scenario. The existence of land / space urban agriculture plays an important role in agricultural production systems and maintain the quality of the environment, because it is a major determinant spacious RTH (green open space) and the results of urban agriculture. In addition, urban farming provides employment and a source of additional revenue as well as environmentally sustainable society.